2016
DOI: 10.1016/j.physrep.2016.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Electrical detection of magnetization dynamics via spin rectification effects

Abstract: The purpose of this article is to review the current status of a frontier in dynamic spintronics and contemporary magnetism, in which much progress has been made in the past decade, based on the creation of a variety of micro-and nano-structured devices that enable electrical detection of magnetization dynamics. The primary focus is on the physics of spin rectification effects, which are well suited for studying magnetization dynamics and spin transport in a variety of magnetic materials and spintronic devices… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
115
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(131 citation statements)
references
References 432 publications
(651 reference statements)
6
115
0
Order By: Relevance
“…It has been reported that the proper separation of the rectification effect from spin pumping can be analyzed by the angular dependence of the voltage . Therefore, we performed the in‐plane angle‐dependent measurements of the voltage at the interval of the 3° between the applied magnetic field and rf field ( φ ).…”
Section: Parameters Used To Get the Best Fit Of The Xrr Data For The mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the proper separation of the rectification effect from spin pumping can be analyzed by the angular dependence of the voltage . Therefore, we performed the in‐plane angle‐dependent measurements of the voltage at the interval of the 3° between the applied magnetic field and rf field ( φ ).…”
Section: Parameters Used To Get the Best Fit Of The Xrr Data For The mentioning
confidence: 99%
“…Therefore, we performed the in‐plane angle‐dependent measurements of the voltage at the interval of the 3° between the applied magnetic field and rf field ( φ ). In order to separate the various components of other galvanometric effects like AMR and AHE we employed the model given by Harder et al and in a recent report by A. Conca et al As per this model, the authors considered these two components of spin rectifications effects i.e., AMR perpendicular (VAsymAMR) and parallel true(VnormalAnormalsnormalynormalmnormalAnormalMnormalRtrue) to the rf‐field and AHE. The expression for measured voltage can be written as VAsym=VAHE cos φ sin Φ+VAsymAMR cos 2φ cos φ+VAsymAMR sin 2φ cos φ, Vsym=Vspcos3φ+VAHEcosφcos Φ+VsymAMRcos2φcosφ+VsymAM…”
Section: Parameters Used To Get the Best Fit Of The Xrr Data For The mentioning
confidence: 99%
“…Further studies have even found that dc current and dc voltage can be generated by the rectification effect of high‐frequency magnetization dynamics. This so‐called spin rectification effect (SRE), which is due to nonlinear coupling between an oscillating current and an oscillating resistance in magnetic structures, provides a novel technique for the study of magnetization dynamics by electrical detection. Due to its high sensitivity and feasibility, the SRE has been widely employed to study ferromagnetic resonance (FMR), spin wave resonance, and domain‐wall resonance in different ferromagnetic materials.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, a dc voltage spectrum was measured by sweeping the bias field at a fixed frequency. By solving the LLG equation, the spectrum can be fitted by the Lorentz and dispersive shape components, and the Lorentz shape is symmetric while the dispersive shape is antisymmetric around the resonance field . However, this method is not suitable if the magnetic domain structure changes with the sweeping of magnetic field during the measurement process, such as in stripe domain structure, in which the magnetic domains will reorientate along the external magnetic field .…”
Section: Introductionmentioning
confidence: 99%
“…Frequency‐dependent voltage is a convenient way to characterize the magnetization dynamics . In Figure (a), the red solid curve denotes the V IREE extracted through the method of sample flipping at different frequencies of the microwave, and the varying magnitude of the V IREE arises from the variation of the phase between the microwave current and magnetization, which is determined by the sample and its holders.…”
mentioning
confidence: 99%